Uterus globulin associated protein 1 (UGRP1) binds podoplanin (PDPN) to promote a novel inflammation pathway during Streptococcus pneumoniae infection - Lei Han; Feifei Zhang; Yu Liu; Jie Yu; Qianyue Zhang; Xiaoping Ye; Huaidong Song; Cuixia Zheng; Bing Han (Clinical and Translational Medicine, 2022)
Abstract Background Streptococcus pneumoniae is the major cause of life‐threatening infections. Toll‐like receptors (TLRs) and NOD‐like receptors (NLRs) could recognise S. pneumoniae and regulate the production of pro‐inflammatory cytokines. UGRP1, highly expressed in lung, is predominantly secreted in airways. However, the function of UGRP1 in pneumonia is mainly unknown. Methods and results We showed that upon TLR2/TLR4/NOD2 agonists stimulation or S. pneumoniae infection, treatment with UGRP1 could promote phosphorylation of p65 and enhance IL‐6, IL‐1β and TNFα production in macrophages. We further elucidated that after binding with cell‐surface receptor PDPN, UGRP1 could activate RhoA to enhance interaction of IKKγ and IKKβ, which slightly activated NF‐κB to improve expression of TLR2, MyD88, NOD2 and NLRP3. Deletion of UGRP1 or blocking UGRP1 interaction with PDPN protected mice against S. pneumoniae‐induced severe pneumococcal pneumonia, and activating RhoA with agonist in UGRP1‐deficient mice restored the reduced IL‐6 production. Conclusion We demonstrated that UGRP1–PDPN–RhoA signaling could activate NF‐κB to promote expression of TLR2, MyD88, NOD2 and NLRP3, which enhanced inflammatory cytokines secretion during S. pneumoniae infection. Antibodies, which could interrupt interaction of UGRP1 and PDPN, are potential therapeutics against S. pneumoniae.